Pengaruh Jenis Pelarut Terhadap Aktivitas Antioksidan Ekstrak Daun Tenggulun (Protium javanicum Burm. F) Menggunakan Metode Maserasi - Yolanda Simamora, Agnes Citra; Yusasrini, Ni Luh Ari; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i04.p13, 2021)
This study was conducted to determine the effect of different solvents on the antioxidant activity of tenggulun leaf extract with the maceration method and to find out the right type of solvent used to extract tenggulun leaf with the highest antioxidant activity. The experimental design used in this study was a Completely Randomized Design (CRD) with various types of solvents as a treatment using maceration method. The treatment consisting of four levels, namely ethanol 90%, aquades, methanol 90%, and acetone 90%. All treatments were repeated four times so that they were obtained 16 experimental units. The data obtained were analyzed by variance and if the treatment affected the observed variables, it was continued with the Duncan’s Multiple Range Test (DMRT). The results showed that the various types of solvent treatments had a very significant effect on antioxidant activity, yields, total phenols, total flavonoids, and total tannins of tenggulun leaf extract. Methanol solvent had the best treatment which produced the highest antioxidant activity 82,36%, IC50 13,52 ppm, yields 7,94%, total phenols 38,56 mg GAE/g, total flavonoids 10,75 mg QE/g, total tannins 5,65 mg TAE/g.